Exploring The Teaching Methodologies Used By English Teachers Iin Teaching pronunciation at English Education Department of Universitas Muhammadiyah Yogyakarta. - Irfan Dwi Yulianto (PBI 14 UMY 006, 2014)
One of the most important parts in English is pronunciation. Pronunciation need to be taught to EFL students to avoid misunderstanding between speakers and listeners. The understanding of the listeners will be shifted if the speakers mispronounce some words. To cope with this importance, the method on how to teach pronunciation is explored in this research. In attempt to conduct the research, the researcher adopted qualitative research design. Three participants were involved in this research. The three participants were teachers of English Education Department of Universitas Muhammadiyah Yogyakarta who had been teaching speaking classes for two years or more. The researcher used in-depth interview, classroom observation, and also member checking to check the validity of the interview. The results of the research showed that teachers in English Education Department adopted integrated teaching pronunciation in speaking class. The teachers used many methods and techniques in teaching pronunciation. The methods adopted by teachers were drilling, direct and indirect correction, minimal pairs, jazz chant, associating Arabic alphabet with English sounds, and teaching pronunciation with phonetic alphabet. Regarding to the problems faced by the teachers, study background first language of the students, rhythm and intonation, references for spoken English, and new words were the major problems faced by the teachers. To overcome those problems, teachers applied drilling for the low level of the students’ English proficiency, used videos as the resource, and some devices to guide the rhythm, intonation, and new words. Keywords: Method, technique, pronunciation.